Vague Norms of Population Density in Land Control Regulation - Sofa, Amalia; Al Uyun, Dhia; Supriyadi (JURNAL USM LAW REVIEW, 2026)
This study aims to examine the vagueness of population density criteria stipulated in Article 3 paragraph (3) of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) No. 18 of 2016 and to formulate a normative reformulation that ensures legal certainty in agricultural land ownership restrictions. The core legal problem lies in the absence of explicit quantitative parameters defining “dense” and “non-dense” areas, which renders the regulation difficult to implement and prone to subjective administrative discretion. Employing normative legal research with a statutory and conceptual approach, this study analyzes the internal coherence of agrarian regulations and evaluates their compatibility with the principle of lex certa. The analysis reveals that the reliance on outdated qualitative demographic classifications, originating from population standards of the 1960s, is no longer responsive to contemporary demographic dynamics and has generated legal uncertainty as well as risks of land ownership concentration. The novelty of this research lies in proposing an operational and prescriptive legal construction that integrates objective population density ratios (persons per km²), based on official data from the Central Statistics Agency (BPS), into the regulatory framework. This quantitative approach replaces elastic qualitative labels with measurable indicators, thereby strengthening transparency, consistency, and enforceability of land control policies. The findings confirm that the absence of numerical benchmarks constitutes a legal loophole that undermines agrarian justice and weakens state control over land ownership. Consequently, the study concludes that reformulating Article 3 paragraph (3) through the incorporation of objective demographic parameters is essential to enhance legal certainty, prevent land monopolization, and reinforce equitable land governance in Indonesia.